A realibus ad realiora, or from a real to the most real (on the characterization of the cinematic image by Andrey Tarkovski) - Sobolevska, Olena (Actual Problems of Mind, 2017)
The author considers the most characteristic features of the works by film director Andrey Tarkovski and explains the specific nature of the cinematic picture created by him. The main conclusion is that Tarkovski duplicates the reality by turning our attention to the full-fledged although devaluated real life. As the result our mind is liberated from a daily routine and form us as a spectator.